Loneliness in Elderly People, Associated Factors and Its Correlation with Quality of Life: A Field Study from Western Turkey - Hülya Arslantaş; Filiz Adana; Filiz Abacigil Ergin; Derya Kayar; Gülçin Acar (Tehran University of Medical Sciences, 2015)
Background: This study examined the factors that affect loneliness of older people and their relationship with quality of life. Methods: Data in this cross-sectional study were collected through survey form, UCLA Loneliness Scale and Quality of Life (QOL) Short Form (SF-36) Scale. The total number of elderly people over the age of 65 yr from whom the study population was chosen was 4,170.The study population was determined as 190 with G-power program by taking impact size 0.362, α=0.05, power (1-β) =0.80 at a confidence level of 95% and a substitute group composing of 10 individuals was added. In total, 83.2% (n=174) of the target population was reached via Multi-Stage Sampling Methods. Results: UCLA Loneliness median score of the participants was 33 (25thp= 27, 75thp= 40). It was found that the existence of chronic diseases and physical handicaps, regular use of medication, lack of hobbies and living with spouse increased loneliness (P<0.05). A negative relationship was identified between all sub-scales in the QOL scale and loneliness. Conclusion: Loneliness negatively affects QOL in old age and that the existence of chronic health problems and lack of hobbies are strong predictors for loneliness. Elderly people living alone must be evaluated as a high-risk group and thus policy makers and health personnel should be aware of the factors that can affect loneliness. In order to increase life quality of the aged population and psychological well-being of the elderly, social support systems must be taken  into account and the elderly should be encouraged to participate in social activities.